Factors related to adherence with the implementation of COVID-19 health protocols in a traditional market traders’ community in East Java, Indonesia - Wahidah; Widyawati, Ika Yuni; Dewi, Lingga Curnia; Liem, Khatijah (Journal of the Pakistan Medical Association, 2023)
Objective: To observe the relationship of perceived seriousness, perceived susceptibility, perceived benefits, perceived barriers and cues to action with adherence to coronavirus disease-2019 protocols among traders. Methods: The descriptive, quantitative, cross-sectional study was conducted from July to August 2021, in Jember Regency, East Java, Indonesia, and comprised traders in a traditional market. Data was collected using a demographic questionnaire, a questionnaire based on the Health Belief Model, and a coronovirus disease-2019 protocol adherence questionnaire after confirming the validity and reliability of the instruments. Results: Of the 332 subjects, 191(57.5%) were females and 141(42.5%) were males. The largest age group was 30-39 years 137(41.3%), followed by 40-49 years in 132(39.8%). Overall, 293(88.3%) subjects had no history of chronic diseases. The main sources of information related to coronavirus disease-2019 were family/friends 84(25.3%), social media 83(25%) and television 82(24.7%). There were significant relationships of perceived susceptibility (p=0.000; r=0.215), perceived seriousness (p=0.004; r=0.157), perceived benefits (p=0.003; r=0.163), perceived barriers (p=0.001; r=-0.178) and cues to action (p=0.002; r=0.168) with protocol adherence. Conclusion: Perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers and cues to action were found to affect a person’s adherence with coronavirus disease-2019 protocols. Keywords: COVID-19 health protocols, Cues, Health belief model, Adherence.